Influência do tipo de membrana de hemodiálise e da sua reutilização nos marcadores de estresse oxidativo - Bertoncello, Iara (2007)
The effects of the dialysis membranes, hemodialysis (HD) session, and dialyzer reuse on markers of oxidative stress were studied. Patients with end stage renal disease who have undergone regular HD treatment three times a week were randomized in two study groups according to the type of HD membrane (cellulose acetate membrane (CA) vs. polysulfone membrane (PS)). All the patients participated of the two study groups and used the two different membranes. To analyze the parameters, the blood samples were colleted before and after HD sessions, in the irst use, 6th, 12th reuse of the membranes. The indicator parameters of oxidative stress analyzed were thiobarbituric acid reactive species (TBARS) and dichlorofluorescein reactive species (DRS) levels, carbonyl groups, antioxidant enzyme (catalase (CAT), superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px)), and non-enzymatic antioxidant (protein (PSH) and non-protein thiol groups (NPSH) and vitamin C). The results demonstrated that there was no significant difference in the markers of oxidative stress between the two membranes used. However, HD session contributed to the increase in TBARS (1st use and the 6th reuse), DRS (6th and 12th reuse), protein (all uses) and NPSH (1st use and 6th reuse) levels, GSH-Px activity (12th reuse) and to the decrease in vitamin C levels (all uses). The dialyzer reuse practice contributed to the increase in the PSH levels, to the decrease in the NPSH levels and to the reduction of the effects of the HD session on the TBARS levels. Therefore, the results obtained from this study revealed that regular HD with CA or PS membranes did not interfere with the oxidative status in the patients. However, HD session may contribute to the increase of oxidative stress and the dialyzer reuse practice appears to be efficient in the reduction of the peroxidation lipidic in these patients